Dielectric composition and electronic component

By introducing RE-Mg-Ti-O segregated particles into the dielectric composition of electronic components, the problem of prone to cracks in electronic components under thermal shock is solved, and higher heat resistance and dielectric properties are achieved.

CN119495509APending Publication Date: 2025-02-21TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410897999.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-18
Filing Date
2024-07-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing electronic components are prone to cracks under thermal shock, resulting in a degradation of the performance of the dielectric composition.

Method used

Using a dielectric composition containing RE-Mg-Ti-O segregated particles, excessive grain growth of the main phase particles is inhibited by RE-Mg-Ti-O segregated particles and its development is stopped when the crack arrives.

Benefits of technology

The cracks generated by thermal shock are effectively suppressed, the heat resistance and thermal conductivity of the dielectric composition are improved, while maintaining a high relative dielectric constant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495509A_ABST
    Figure CN119495509A_ABST
Patent Text Reader

Abstract

The invention relates to a dielectric composition and an electronic component. The dielectric composition includes main phase particles and segregation particles, at least a part of the segregation particles are RE-Mg-Ti-O segregation particles containing RE element, Mg, Ti, and O, the RE element is a rare earth element, the total of the RE element, Mg, and Ti contained in the RE-Mg-Ti-O segregation particles is 70 parts by mole or more when the total of the metal elements contained in the RE-Mg-Ti-O segregation particles is 100 parts by mole, and the total of the RE element, Mg, and Ti contained in the RE-Mg-Ti-O segregation particles is 70 parts by mole or more when the total of the metal elements contained in the RE-Mg-Ti-O segregation particles is 100 parts by mole. The ratio of Mg to the total of the RE element and Mg in the RE-Mg-Ti-O segregated particles is 0.1 to 0.3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority based on Japanese Patent Application No. 2023-133534 filed on August 18, 2023, and the entirety of the disclosure is incorporated into this specification by reference.

[0002] The present invention relates to a dielectric composition and an electronic component including a dielectric layer composed of the dielectric composition. Background Art

[0003] Electronic components such as multilayer ceramic capacitors that utilize dielectric properties exhibited by dielectrics are mounted in electronic circuits or power supply circuits incorporated in electronic devices. Patent document 1 (Japanese Patent Publication No. 2001-6966) discloses that the main component of dielectric ceramics of electronic components is a composition represented by the general formula ABO3 (wherein A is at least one of Ba, Sr, Ca and Mg, and B is at least one of Ti, Zr and Hf).

[0004] The conventional electronic components shown in Patent Document 1 are mounted on a circuit board or the like by a method such as "reflow soldering" or "flow soldering". Compared with "reflow soldering", "flow soldering" has the advantage of being inexpensive, but when mounted on a substrate by "flow soldering", cracks may occur in the dielectric composition (dielectric ceramic) of the electronic component due to thermal shock or the like. Therefore, it is desired to develop a dielectric composition that can effectively prevent cracks due to thermal shock or the like. Summary of the invention

[0005] Technical problem to be solved by the invention

[0006] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide a dielectric composition capable of suppressing cracks caused by thermal shock or the like.

[0007] Solutions for solving technical problems

[0008] In order to achieve the above object, the dielectric composition involved in the present invention is a dielectric composition comprising main phase particles and segregation particles, wherein:

[0009] At least a portion of the segregated particles are RE-Mg-Ti-O segregated particles containing RE elements, Mg, Ti and O.

[0010] The RE element is a rare earth element,

[0011] When the total amount of metal elements contained in the RE-Mg-Ti-O segregated particles is 100 parts by mole, the total amount of RE elements, Mg and Ti contained in the RE-Mg-Ti-O segregated particles is 70 parts by mole or more.

[0012] The ratio of Mg in the RE-Mg-Ti-O segregated particles to the total of the RE element and Mg is 0.1 to 0.3.

[0013] The present inventors have conducted intensive studies on a dielectric composition capable of suppressing cracks caused by thermal shock or the like, and as a result have found that a dielectric composition having RE-Mg-Ti-O segregated particles has an excellent crack suppressing effect, thereby completing the present invention.

[0014] It is considered that the reason why cracks caused by thermal shock or the like can be suppressed by RE-Mg-Ti-O segregated particles is that, for example, the RE-Mg-Ti-O segregated particles suppress excessive grain growth of main phase particles.

[0015] In addition, it is considered that even if cracks were generated in the dielectric composition, the cracks reached the RE-Mg-Ti-O segregation particles, thereby stopping the crack growth.

[0016] The RE-Mg-Ti-O segregation particles may exist at the grain boundaries of the main phase particles.

[0017] Preferably, the average particle size of the RE-Mg-Ti-O segregated particles is 0.1 μm or less.

[0018] Preferably, when observing a total of 5 μm 2 When the cross section of the dielectric composition is observed, the RE-Mg-Ti-O segregated particles are observed to be 0.2 to 2 particles / μm on average. 2 .

[0019] By making the RE-Mg-Ti-O segregation particles finer and increasing the surface area, the surface energy can be increased, so even if only a small amount of RE-Mg-Ti-O segregation particles are included, the movement of the grain boundaries of the main phase particles can be effectively suppressed, and the excessive grain growth of the main phase particles can be further suppressed. As a result, cracks can be made less likely to occur.

[0020] In addition, since the RE-Mg-Ti-O segregated particles are small in number, the RE-Mg-Ti-O segregated particles do not completely block the main phase particles, so that heat conduction between the main phase particles is easy, and the thermal conductivity of the dielectric composition as a whole is also increased, and the thermal shock resistance is enhanced. As a result, cracks caused by thermal shock can be further suppressed.

[0021] Furthermore, when the average number of RE-Mg-Ti-O segregated particles is within the above range, a high relative dielectric constant can be maintained compared to a case where the average number of RE-Mg-Ti-O segregated particles is within the above range, since the main phase particles that mainly exert dielectric properties are sufficiently present in the dielectric composition, the relative dielectric constant is considered to be high.

[0022] Preferably, the main phase particles are composed of BaTiO3.

[0023] Preferably, the composition of the RE-Mg-Ti-O segregation particles is {RE (1-a) Mg a}2Ti2O 7-a , wherein a is 0.1 to 0.3.

[0024] The electronic component of the present invention includes a dielectric layer containing the dielectric composition of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1A It is a cross-sectional view of a multilayer ceramic capacitor according to one embodiment of the present invention.

[0026] Figure 1B It is along Figure 1A A cross-sectional view of an IB-IB line stacked ceramic capacitor.

[0027] Figure 2 It is a schematic diagram of a cross section of a dielectric composition according to one embodiment of the present invention.

[0028] Explanation of symbols:

[0029] 1…Multilayer ceramic capacitor

[0030] 10…Component body

[0031] 2…Dielectric layer

[0032] 20…Main phase particles

[0033] 22…RE-Mg-Ti-O segregation particles

[0034] 28…Grain boundary

[0035] 3…Internal electrode layer

[0036] 4…External electrode DETAILED DESCRIPTION

[0037] <Multilayer Ceramic Capacitors>

[0038] Figure 1A and Figure 1BA laminated ceramic capacitor 1 is shown as an example of an electronic component of the present embodiment. The laminated ceramic capacitor 1 has a component body 10 having a structure in which dielectric layers 2 and internal electrode layers 3 are alternately laminated. A pair of external electrodes 4 are formed at both ends of the component body 10, and the pair of external electrodes 4 are respectively connected to the internal electrode layers 3 alternately arranged inside the component body 10. The shape of the component body 10 is not particularly limited, and is usually set to a rectangular parallelepiped. In addition, the size of the component body 10 is not particularly limited, as long as it is set to an appropriate size according to the purpose.

[0039] In this embodiment, the longitudinal dimension L0 of the element body 10 (see Figure 1A ) is preferably 3.5 to 0.4 mm. In this embodiment, the width dimension W0 of the element body 10 (see Figure 1B ) is preferably 2.7 to 0.2 mm.

[0040] As specific dimensions of the element body 10, L0×W0 may be (3.2±0.3) mm×(2.5±0.2) mm, (3.2±0.3) mm×(1.6±0.2) mm, (2.0±0.2) mm×(1.2±0.1) mm, (1.6±0.2) mm×(0.8±0.1) mm, (1.0±0.1) mm×(0.5±0.05) mm, (0.6±0.06) mm×(0.3±0.03) mm, (0.4±0.04) mm×(0.2±0.02) mm, etc. In addition, H0 is not particularly limited, and may be, for example, equal to or less than W0.

[0041] The dielectric layer 2 is composed of a dielectric composition of the present embodiment described later.

[0042] The thickness of each layer of the dielectric layer 2 (interlayer thickness) is not particularly limited and can be arbitrarily set according to the desired characteristics, application, etc. Generally, the interlayer thickness is preferably 30 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less. In addition, the number of stacked layers of the dielectric layer 2 is not particularly limited, but in the present embodiment, for example, it is preferably 20 or more.

[0043] In the present embodiment, the internal electrode layers 3 are stacked so that the respective end portions are alternately exposed on the surfaces of two opposing end faces of the element body 10 .

[0044] The thickness of the internal electrode layer 3 is not particularly limited, but is, for example, 2 μm or less, and preferably 1.5 μm or less.

[0045] There is no particular limitation on the conductive material contained in the internal electrode layer 3. Examples of the noble metal used as the conductive material include Pd, Pt, and Ag-Pd alloys. Examples of the base metal used as the conductive material include Ni, Ni alloys, Cu, and Cu alloys. In addition, various trace components such as P and / or S may be contained in Ni, Ni alloys, Cu, or Cu alloys in an amount of less than 0.1 mass %. In addition, the internal electrode layer 3 may also be formed using a commercially available electrode paste. The thickness of the internal electrode layer 3 may be appropriately determined according to the intended use, etc.

[0046] The conductive material contained in the external electrode 4 is not particularly limited. For example, a known conductive material such as Ni, Cu, Sn, Ag, Pd, Pt, Au or alloys thereof, conductive resin, etc. can be used. The thickness of the external electrode 4 can be appropriately determined according to the application, etc.

[0047] <Dielectric composition>

[0048] like Figure 2 As shown, the dielectric composition constituting the dielectric layer 2 includes main phase particles 20 and RE-Mg-Ti-O segregation particles 22. The RE-Mg-Ti-O segregation particles 22 contain RE elements, Mg, Ti, and O. Here, "RE elements" refer to rare earth elements. The RE-Mg-Ti-O segregation particles 22 may also exist at the grain boundaries 28 of the main phase particles 20.

[0049] In the present embodiment, as long as at least a portion of the segregated particles contained in the dielectric composition are the RE-Mg-Ti-O segregated particles 22 , the dielectric composition may include segregated particles having a composition other than the RE-Mg-Ti-O segregated particles 22 .

[0050] <Main phase particles>

[0051] The main phase particles 20 of this embodiment contain a compound represented by AMO 3 as a main component. The main component of the main phase particles 20 is a component that accounts for 80 to 100 parts by mass, preferably 90 to 100 parts by mass, based on 100 parts by mass of the main phase particles 20.

[0052] The molar ratio of the A element to the M element represented by (molar ratio of A / molar ratio of M) may be 1 or may not be 1. (molar ratio of A / molar ratio of M) is preferably 0.9 to 1.2.

[0053] The element A contains at least one selected from Ba and Ca. The element A is preferably Ba. Thus, the dielectric composition can exhibit a higher relative dielectric constant.

[0054] When the element A is Ba and Ca, the content of Ba is preferably 0.9 to 1 part by mole, based on 1 part by mole of the total of Ba and Ca.

[0055] The M element contains at least one selected from Ti and Zr. The M element is preferably Ti. Thus, the dielectric composition can exhibit a higher relative dielectric constant.

[0056] When the M element is Ti and Zr, the content of Ti is preferably 0.8 to 1 part by mole, based on 1 part by mole of the total of Ti and Zr.

[0057] The main phase grains 20 may further contain Mg, Mn, Cr, Si, RE elements, V, Li, B, Al, and the like.

[0058] <RE-Mg-Ti-O segregation particles>

[0059] The RE-Mg-Ti-O segregation particles 22 contain RE elements, Mg, Ti, and O.

[0060] "RE element" means a rare earth element. The type of RE element is not particularly limited, and for example, Y, Dy, or Ho can be used. The RE element may be used alone or in combination of two or more.

[0061] When the total amount of metal elements contained in the RE-Mg-Ti-O segregation particles 22 is 100 parts by mole, the total amount of the RE element, Mg, and Ti contained in the RE-Mg-Ti-O segregation particles 22 is 70 parts by mole or more.

[0062] The ratio of Mg in the RE-Mg-Ti-O segregated particles 22 to the total of the RE element and Mg {Mg / (RE+Mg)} is 0.1 to 0.3.

[0063] The ratio of Ti to the total of the RE element and Mg {Ti / (RE+Mg)} in the RE-Mg-Ti-O segregated particles 22 is preferably 0.7 to 1.3.

[0064] The composition of the RE-Mg-Ti-O segregation particles 22 is not particularly limited, and may be, for example, {RE (1-a) Mg a}2Ti2O 7-a , a can also be 0.1~0.3.

[0065] The average particle size of the RE-Mg-Ti-O segregated particles 22 is preferably 0.1 μm or less, and more preferably 0.05 μm or less. The average particle size of the RE-Mg-Ti-O segregated particles 22 may be an average of the equivalent circle diameters of the RE-Mg-Ti-O segregated particles 22 .

[0066] In total, 5 μm 2 When the cross section of the dielectric composition is observed, it is preferable that the RE-Mg-Ti-O segregation particles 22 are observed at an average of 0.2 to 2 particles / μm. 2 More preferably, 0.5 to 1.5 pieces / μm are observed 2 Here, for "observing a total of 5μm 2 When the cross section of the dielectric composition is observed, the observation field is 1 field, which means "observation of 5 μm 2 When the observation field is two or more, it means "the total area of ​​each field of view is 5 μm 2 In the above cases, when observing separately in each field of view".

[0067] In addition, regarding the RE-Mg-Ti-O segregated particles 22, all the segregated particles included in one field of view are counted as 1. For example, the RE-Mg-Ti-O segregated particles 22 observed at one end of the field of view and partially missing are not counted.

[0068] The crystal system of the RE-Mg-Ti-O segregated particles 22 is preferably a tetragonal system.

[0069] The space group of the RE-Mg-Ti-O segregation particles 22 is preferably

[0070] <Method for Confirming Segregated Particles>

[0071] The method for determining whether or not the dielectric composition constituting the dielectric layer 2 has the RE-Mg-Ti-O segregated particles 22 is not particularly limited, and a specific method is exemplified below.

[0072] First, a cross section of the dielectric composition is photographed using a scanning transmission electron microscope (STEM) to obtain a dark field (DF) image. The width of the photographed field of view is not particularly limited, and is, for example, about 1 to 10 μm square. The region having a contrast different from that of the main phase particles 20 in the dark field image is identified as a heterogeneous phase. Whether there is a different contrast, that is, whether there is a heterogeneous phase, can be determined by visual observation or by software for image processing.

[0073] Then, various elements were measured for the above-mentioned heterogeneous phase by energy dispersive X-ray analysis (EDS analysis).

[0074] When RE elements, Mg, Ti and O exist at the same position of the heterophase, and when the total amount of metal elements in the heterophase is set to 100 mol parts, the total amount of RE elements, Mg and Ti in the heterophase is more than 70 mol parts, and Mg / (RE+Mg) in the heterophase is 0.1 to 0.3, the heterophase can be judged to be RE-Mg-Ti-O segregation particles 22.

[0075] In addition, it can be determined that the particles are RE-Mg-Ti-O segregation particles 22 from the element mapping image.

[0076] <Method for manufacturing multilayer ceramic capacitor>

[0077] Next, the following description Figure 1A and Figure 1B An example of a method for manufacturing the multilayer ceramic capacitor 1 is shown.

[0078] In the present embodiment, a calcined powder of a raw material mixture of calcined powder of AMO 3 which is a main component constituting the main phase particles 20 of the above-mentioned dielectric composition and RE-Mg-Ti-O segregated particles 22 is prepared.

[0079] The calcined powder of AMO3 is calcined powder of the A element and the M element which constitute the main phase particles 20 after firing.

[0080] The calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 is a calcined powder of the RE element, Mg, and Ti that constitute the RE-Mg-Ti-O segregated particles 22 after firing.

[0081] As the raw material of each element mentioned above, there is no particular limitation, and the oxide of each element can be used. In addition, various compounds that can obtain the oxide of each element by calcination can be used. As various compounds, examples such as carbonates, oxalates, nitrates, hydroxides, organometallic compounds, etc. can be exemplified. In the present embodiment, the above-mentioned starting raw material is preferably a powder.

[0082] After weighing the raw materials of AMO3 particles in the prepared starting materials according to a prescribed ratio, wet mixing is performed for a prescribed time using a ball mill or the like. After the mixed powder is dried, heat treatment is performed in the air at a temperature of 700 to 1300° C. to obtain a calcined powder of the raw material mixture of AMO3 particles. Alternatively, the calcined powder may be crushed for a prescribed time using a ball mill or the like.

[0083] Various compounds such as oxides of the elements constituting the RE-Mg-Ti-O segregated particles 22 after firing are prepared, and after heat treatment, they are pulverized for a predetermined time using a ball mill or the like to obtain a calcined powder of a raw material mixture of the RE-Mg-Ti-O segregated particles 22 .

[0084] For example, the particle size of the RE-Mg-Ti-O segregated particles 22 can be changed by changing the pulverization time. The longer the pulverization time, the smaller the particle size of the RE-Mg-Ti-O segregated particles 22. In addition, the particle size of the RE-Mg-Ti-O segregated particles 22 can also be changed by changing the media diameter of the ball mill.

[0085] Next, a paste for making green chips is prepared. The calcined powder of the raw material mixture of the obtained AMO3 particles, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22, a binder, and a solvent are kneaded and coated to prepare a paste for the dielectric layer. The binder and the solvent can be any known material.

[0086] The dielectric layer paste may contain additives such as a plasticizer and a dispersant as necessary.

[0087] The internal electrode layer paste is obtained by kneading the above-mentioned conductive material raw materials, a binder, and a solvent. The binder and the solvent may be known materials. The internal electrode layer paste may also contain additives such as general materials or plasticizers as needed.

[0088] The external electrode paste can be prepared in the same manner as the internal electrode layer paste.

[0089] Green sheets are formed using the obtained pastes, and internal electrode patterns are formed on the green sheets to obtain a laminated body. Next, the laminated body is cut to obtain green chips.

[0090] The obtained green chip is subjected to a binder removal treatment as necessary. The binder removal treatment conditions are preferably set at a holding temperature of 200 to 350°C, for example.

[0091] After the binder removal treatment, the green chip is fired to obtain the element body 10. In this embodiment, the atmosphere during firing is not particularly limited, and it can be in air or in a reducing atmosphere. In this embodiment, the holding temperature during firing is not particularly limited, and is, for example, 1200 to 1350°C.

[0092] After firing, the obtained element body 10 is subjected to reoxidation treatment (annealing) as necessary. For example, the annealing conditions preferably set the oxygen partial pressure during annealing to be higher than the oxygen partial pressure during firing and set the holding temperature to be 1150° C. or lower.

[0093] The dielectric composition constituting the dielectric layer 2 of the element body 10 obtained as described above is the above-mentioned dielectric composition. The element body 10 is subjected to end surface grinding, and an external electrode paste is applied and sintered to form the external electrode 4. Then, if necessary, a coating layer is formed on the surface of the external electrode 4 by plating or the like.

[0094] In this manner, the multilayer ceramic capacitor 1 of the present embodiment is manufactured.

[0095] <Summary of this embodiment>

[0096] One of the causes of cracks in the dielectric composition is "excessive grain growth of the main phase particles 20". That is, due to the excessive grain growth of the main phase particles 20, pores are easily generated in the dielectric composition, and due to the application of thermal shock such as "flow welding", cracks may sometimes be generated starting from the pores.

[0097] Therefore, in order to suppress cracking of the dielectric composition, it is desirable to suppress excessive grain growth of the main phase particles 20 .

[0098] As one method of suppressing excessive grain growth of the main phase particles 20, a method of using the "pinning effect by the second phase particles" can be cited. Here, the "pinning effect" is a phenomenon in which the movement of the grain boundaries 28 is suppressed by the second phase particles, thereby suppressing the grain growth of the first phase particles (the main phase particles 20 in this embodiment). Therefore, the present inventors have studied a method of making particles that become second phase particles exist in the dielectric composition.

[0099] First, RE2O3 or MgO, when used as a single substance, is easily dissolved in AMO3, and therefore, may be dissolved in AMO3. Therefore, RE2O3 or MgO, when used as a single substance, is unlikely to exist as second phase particles that exert a pinning effect in a dielectric composition.

[0100] Furthermore, RE2O3 and MgO form a solid solution, MgO replaces a part of RE2O3, and RE2O3 replaces a part of MgO, but no compounds other than these are formed. Therefore, similar to the behavior of RE2O3 or MgO monomers, the solid solution of RE2O3 and MgO will also dissolve in AMO3, so the solid solution of RE2O3 and MgO is also difficult to exist as a second phase particle that exerts a pinning effect in the dielectric composition.

[0101] Therefore, the present inventors have found that RE-Mg-Ti-O segregation particles 22 are formed from RE2O3, MgO and TiO2 to become second phase particles. The RE-Mg-Ti-O segregation particles 22 are stable compounds, and therefore are considered to be less soluble in the main phase particles 20 containing AMO3 as a main component. Therefore, by the presence of the RE-Mg-Ti-O segregation particles 22 at the grain boundaries 28 of the main phase particles 20, the movement of the grain boundaries 28 of the main phase particles 20 can be effectively suppressed by the pinning effect, and the grain growth of the main phase particles 20 can be suppressed. As a result, cracks caused by thermal shock or the like can be less likely to occur.

[0102] Furthermore, even if cracks are generated in the dielectric composition, the cracks can be stopped from developing when the cracks reach the RE-Mg-Ti-O segregation particles 22. In other words, the cracks can be stopped from developing by the RE-Mg-Ti-O segregation particles 22.

[0103] Furthermore, by making the RE-Mg-Ti-O segregation particles 22 finer and increasing the surface area, the surface energy can be increased. Therefore, even if only a small amount is included between the main phase particles 20, the movement of the grain boundaries 28 of the main phase particles 20 can be effectively suppressed, the grain growth of the main phase particles 20 can be suppressed, cracks are less likely to occur, and the development of cracks can be stopped by the RE-Mg-Ti-O segregation particles 22.

[0104] Furthermore, when there are a small number of RE-Mg-Ti-O segregated particles 22, the main phase particles 20 are not completely blocked, so that heat conduction is easily performed between the main phase particles 20, and the thermal conductivity of the dielectric composition as a whole is also increased, and the thermal shock resistance is enhanced. As a result, cracks caused by thermal shock can be further suppressed.

[0105] As mentioned above, although embodiment of this invention is described, this invention is not limited to the said embodiment at all, It can also change in various aspects within the scope of this invention.

[0106] In the above-mentioned embodiment, the case where the electronic component of the present invention is a multilayer ceramic capacitor has been described. However, the electronic component of the present invention is not limited to a multilayer ceramic capacitor, and any electronic component may be used as long as it includes the above-mentioned dielectric composition.

[0107] For example, a single-plate type ceramic capacitor in which a pair of electrodes are formed in the above-mentioned dielectric composition may be used.

[0108] Example

[0109] Hereinafter, the present invention will be described in more detail using examples and comparative examples. However, the present invention is not limited to the following examples.

[0110] As starting materials for the main phase particles 20 contained in the dielectric composition, powders of BaCO3, CaCO3, ZrO2, and TiO2 were prepared. The prepared starting materials were weighed so that the main components of the main phase particles 20 after sintering were as shown in Tables 1, 2, and 4.

[0111] Next, the weighed powders were wet-mixed for 16 hours using ion exchange water as a dispersion medium using a ball mill, and the mixture was dried to obtain a mixed raw material powder. Then, the obtained mixed raw material powder was heat-treated in the atmosphere at a temperature of 1000° C. for 2 hours, and wet-pulverized for 16 hours using ion exchange water as a dispersion medium using a ball mill, and the mixture was dried to obtain a calcined powder of the raw material mixture of the main phase particles 20.

[0112] In addition, powders of oxides of RE elements (Y2O3), MgCO3, and TiO2 were prepared as raw materials for the RE-Mg-Ti-O segregated particles 22. The prepared starting raw materials were weighed so that "Ti / (RE+Mg)" and "Mg / (RE+Mg)" of the RE-Mg-Ti-O segregated particles 22 were as described in Tables 1, 2, and 4, and the amount of the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 (unit: parts by mass) (described as "addition amount" in Tables 1, 2, and 4) added relative to 100 parts by mass of the calcined powder of the raw material mixture of the main phase particles 20 was as described in Tables 1, 2, and 4.

[0113] In addition, powders of RE element oxide (Y2O3), MgCO3, and TiO2 were prepared as raw materials for the RE-Mg-Ti-O segregated particles 22. The prepared powders were weighed so that "Ti / (RE+Mg)" and "Mg / (RE+Mg)" of the RE-Mg-Ti-O segregated particles 22 were as shown in Tables 1, 2, and 4.

[0114] Next, the weighed powders were wet-mixed for 16 hours in a ball mill using ion exchange water as a dispersion medium, the mixture was dried, and heat-treated in the atmosphere at a temperature of 1000° C. for 2 hours, wet-crushed for 16 hours in a ball mill using ion exchange water as a dispersion medium, and the mixture was dried to obtain a calcined powder of the raw material mixture of RE-Mg-Ti-O segregation particles 22.

[0115] Further, inorganic additives are prepared by the following method. First, using ion exchange water as a dispersion medium, each powder of MgCO3, Y2O3, MnCO3, SiO2 and V2O5 is wet mixed for 16 hours using a ball mill to obtain a mixture. Then, the mixture is dried and heat-treated in the atmosphere at a temperature of 900°C for a retention time of 2 hours. Using ion exchange water as a dispersion medium, the heat-treated mixture is wet-pulverized for 16 hours using a ball mill and dried to obtain an inorganic additive.

[0116] Next, the calcined powder of the raw material mixture of the main phase particles 20, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22, the inorganic additive, the binder, and the solvent are kneaded and coated to prepare a dielectric layer paste. Here, the prepared starting materials are weighed so that the addition amount (unit: mass part) of the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 is as described in Tables 1, 2, and 4 relative to 100 parts by mass of the calcined powder of the raw material mixture of the main phase particles 20 (described as "addition amount" in Tables 1, 2, and 4).

[0117] 56 parts by mass of nickel particles, 40 parts by mass of terpineol, 4 parts by mass of ethyl cellulose (molecular weight: 140,000), and 1 part by mass of benzotriazole were kneaded and paste-formed using a triple roll to prepare an internal electrode layer paste.

[0118] Then, the dielectric layer paste prepared in the above manner was used to form a green sheet on a PET film, and the internal electrode layer paste was screen-printed to form a green sheet.

[0119] A plurality of green sheets are stacked and bonded under pressure to produce a green stack, and the green stack is cut into a predetermined size to obtain a green chip.

[0120] The obtained green chip is subjected to a binder removal treatment, fired in a reducing atmosphere, and further annealed to obtain a sintered body (dielectric composition) fired in a reducing atmosphere. For the firing conditions, the heating rate is set to 200°C / h, the holding temperature is set to 1250°C, and the holding time is set to 2 hours. The atmosphere gas is set to a mixed gas of nitrogen and hydrogen (hydrogen concentration 3%) humidified to a dew point of 20°C. In addition, for the annealing conditions, the holding temperature is set to 1050°C, and the holding time is set to 2 hours. The atmosphere gas is set to nitrogen humidified to a dew point of 20°C.

[0121] The element body 10 obtained as described above is subjected to end surface grinding, and an external electrode paste is applied and fired to form the external electrodes 4 .

[0122] In this manner, a multilayer ceramic capacitor 1 (hereinafter referred to as a “capacitor sample”) was obtained.

[0123] <Observation of main phase particles>

[0124] The main phase particles 20 were identified by STEM in a 1.7 μm×1.7 μm field of view of the cross section of the dielectric composition of the obtained capacitor sample, and the main components of the main phase particles 20 were identified by EDS. The results are shown in Tables 1, 2, and 4.

[0125] <Observation of segregated particles>

[0126] In a 1.7 μm×1.7 μm field of view of a cross section of the dielectric composition of the obtained capacitor sample, heterogeneous phases were identified by STEM, and the amounts of Y, Mg, and Ti were measured by EDS.

[0127] When Y, Mg and Ti exist at the same position and the total amount of metal elements contained in the heterogeneous phase is 100 parts by mole, if the total amount of Y, Mg and Ti is 70 parts by mole or more and Mg / (RE+Mg) is 0.1 to 0.3, the heterogeneous phase is judged to be RE-Mg-Ti-O segregation particles 22. The presence or absence of RE-Mg-Ti-O segregation particles 22, Ti / (RE+Mg) and Mg / (RE+Mg) are shown in Tables 1, 2 and 4. In addition, in each capacitor sample having RE-Mg-Ti-O segregation particles 22, it was confirmed that the RE-Mg-Ti-O segregation particles 22 exist at the grain boundaries 28 of the main phase particles 20.

[0128] <320℃ thermal shock test>

[0129] In a solder bath heated to 320°C, the capacitor sample was immersed in flux, and then the capacitor sample was held with tweezers and immersed. Then, after taking out the capacitor sample, it was ultrasonically cleaned with a diluent, and the appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Table 1, Table 3, and Table 5.

[0130] <Average particle size>

[0131] The average particle size was measured for each sample in Table 3 and Table 5. Specifically, the total particle size of 5 μm was observed. 2 The cross-section of the dielectric composition described above was observed, and the circle equivalent diameter of the Y-Mg-Ti-O segregated particles 22 was measured, and the measured values ​​were averaged to obtain the average particle size of the Y-Mg-Ti-O segregated particles 22. The results are shown in Tables 3 and 5.

[0132] <350℃ thermal shock test>

[0133] A 350°C heat shock test was performed on each sample in Table 3 and Table 5. Specifically, after the capacitor sample was immersed in flux, it was dipped in a solder bath heated to 350°C by pinching the capacitor sample with tweezers. Then, after taking out the capacitor sample, it was ultrasonically cleaned with a diluent and the appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Table 3 and Table 5.

[0134] <380℃ thermal shock test>

[0135] A 380°C heat shock test was performed on each sample in Table 3 and Table 5. Specifically, after the capacitor sample was immersed in flux, it was dipped in a solder bath heated to 380°C by pinching the capacitor sample with tweezers. Then, after taking out the capacitor sample, it was ultrasonically cleaned with a diluent and the appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Table 3 and Table 5.

[0136] <Average number of particles>

[0137] The average number of particles was measured for each sample in Table 5. Specifically, the total number of particles was 5 μm. 2 The average number of RE-Mg-Ti-O segregated particles 22 observed in the cross section of the above dielectric composition was calculated. The results are shown in Table 5.

[0138] <Relative dielectric constant>

[0139] The relative dielectric constant was measured for each sample in Table 5. Specifically, for the capacitor sample, at room temperature (20°C), a digital LCR meter (4284A manufactured by YHP Co.) was used to input a signal with a frequency of 1 kHz and an input signal level (measurement voltage) of 1 Vrms to measure the capacitance C. Then, the relative dielectric constant was calculated based on the thickness of the sintered body, the effective electrode area, and the capacitance C obtained from the measurement results. The results are shown in Table 5.

[0140] [Table 1]

[0141]

[0142] [Table 2]

[0143]

[0144] [Table 3]

[0145]

[0146] [Table 4]

[0147]

[0148] [Table 5]

[0149]

[0150] According to Table 1, it can be confirmed that the results of the 320°C heat shock test are good when the dielectric composition has RE-Mg-Ti-O segregated particles (sample numbers 5 to 7, 9, 10) compared to the case where the dielectric composition does not have RE-Mg-Ti-O segregated particles (sample numbers 1 to 4, 8).

Claims

1. A dielectric composition, wherein: The dielectric composition comprises main phase particles and segregation particles, At least a portion of the segregated particles are RE-Mg-Ti-O segregated particles containing RE elements, Mg, Ti and O. The RE element is a rare earth element, When the total amount of metal elements in the RE-Mg-Ti-O segregated particles is 100 parts by mole, the total amount of RE elements, Mg and Ti in the RE-Mg-Ti-O segregated particles is 70 parts by mole or more. The ratio of Mg in the RE-Mg-Ti-O segregated particles to the total of the RE element and Mg is 0.1 to 0.

3.

2. The dielectric composition according to claim 1, wherein The RE-Mg-Ti-O segregation particles exist at the grain boundaries of the main phase particles.

3. The dielectric composition according to claim 1, wherein The average particle size of the RE-Mg-Ti-O segregated particles is less than 0.1 μm.

4. The dielectric composition according to claim 1, wherein In total, 5 μm 2 When the cross section of the dielectric composition is observed, the RE-Mg-Ti-O segregated particles are observed to be 0.2 to 2 particles / μm on average. 2 .

5. The dielectric composition according to claim 1, wherein The main phase particles are composed of BaTiO3.

6. The dielectric composition according to claim 1, wherein The composition of the RE-Mg-Ti-O segregation particles is {RE (1-a) Mg a }2Ti2O 7-a , The a is 0.1 to 0.

3.

7. An electronic component, wherein: A dielectric composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Ceramic capacitor and its manufacture

    JP2001006966A

  • Disaster-prevention facility

    JP2023133534A